Structural modulation of the photophysical and electronic properties of pyrene-based 3D metal–organic frameworks derived from s-block metals. Issue 1 (13th November 2020) - Coleman, Christopher N.; Tapping, Patrick C.; Huxley, Michael T.; Kee, Tak W.; Huang, David M.; Doonan, Christian J.; Sumby, Christopher J.
Abstract : Materials in which charge delocalization and migration can be tuned are critical for electronic applications. Abstract : Materials in which charge delocalization and migration can be tuned are critical for electronic applications. Crystalline framework materials containing π-rich polycyclic aromatic moieties, such as pyrene, can provide a pathway for fast anisotropic charge transport. The extent of interchromophore interaction for structurally distinct assemblies of the π-conjugated aromatic ligand 4, 4′, 4′′, 4′′′-(1, 3, 6, 8-pyrenetetrayl) tetrabenzoic acid (H4 TBAPy) was studied within two novel metal–organic frameworks (MOFs), Na(TBAPy)(DMF) and K(TBAPy)(DMF), via steady-state and time-resolved spectroscopic techniques. Single-crystal X-ray diffraction was used to determine the structures of K(TBAPy)(DMF) and Na(TBAPy)(DMF), which both form 3D MOFs comprising 1D rod-like SBUs surrounded by columnar stacks of TBAPy that are aligned in an eclipsed and x-shaped (staggered) geometry, respectively. Spectroscopic and computational results indicate significant chromophore interactions and potentially fast charge transport. Furthermore, distinct transient emission decay profiles are observed and are attributed to significant differences in the stacking orientation of the organic ligands in the two MOFs. Lastly, the study identifies design principles that may be exploited in the rational construction of s-block based MOFs for microelectronic and sensing applications.